Politics of Enfleshment: Corporativity and Hegemony. Castro-Gómez Reader of Laclau-Mouffe - Soto Morera, Diego A. (2020)
AbstractThis article analyzes the reception of Laclau-Mouffe’s hegemonic theory in the political philosophy of the Colombian philosopher Santiago Castro-Gómez. Thepurpose of this academic exercise is to ponder the distinction between the concepts of body and flesh within political theories that think from an agonistic foundation of social relations. To fulfill this objective, not only is Castro-Gómez’s reading of the Laclau-Mouffe project reconstructed, but I also propose an analysis of what the Colombian considers its main limitation: the linguistic reductionism of politics. Within this discussion, I consider it essential to introduce a consideration of the place of the incarnation in the theory of the last Laclau. The text proposes that a consideration of the political struggles and their conquests requires a consideration, not only of the corporate character of the social movements, but also of those aspirations regarding the absent or not occurred that nurture social aspirations and demands. Keywords: Hegemony, Laclau-Mouffe, Castro-Gómez, Antagonism, Enfleshmet